Magnetic properties of nanoparticles of cobalt chromite - Rath C.; Mohanty P.; Banerjee A. (My University, 2025)
Magnetic properties of cobalt chromite nanoparticles of size 812 nm synthesized through conventional coprecipitation route are reported. Magnetization versus temperature measurement plot reveals a transition from paramagnetic to superparamagnetic (SPM) phase in contrast with the transition from paramagnetic to long-range ferrimagnetic phase at Curie temperature, T c, reported in bulk. The blocking temperature, Tb, of SPM phase is found to be 5060 K. On cooling in the presence of 10 kOe field these nanoparticles show an enhancement in coercivity and shifting of loop at 10 K, which is absent at 50 K. While the later observation supports the blocking temperature of the SPM phase, the former one is attributed to a disordered spin configuration at the surfaces and the distribution of nanoparticle sizes. © 2011 Elsevier B.V.